Horrible bosses [videorecording (DVD)] - Day, Charlie; Bateman, Jason; Sudeikis, Jason; Aniston, Jennifer; Farrell, Colin, 1976-; Foxx, Jamie; Spacey, Kevin; Sutherland, Donald, 1935-2024 (Distributed by Warner Home Video, 2011)
"For Nick (Jason Bateman), Kurt (Jason Sudeikis) and Dale (Charlie Day), the only thing that would make the daily grind more tolerable would be to grind their intolerable bosses into dust. Quitting is not an option, so, with the benefit of a few too many drinks and some dubious advice from a hustling ex-con, the three friends devise a convoluted and seemingly foolproof plan to rid themselves of their respective employers-- permanently. There's only one problem: even the best-laid plans are only as foolproof as the brains behind them"--Container.